Artificial guide stars for adaptive optics using unmanned aerial vehicles. Issue 2 (24th March 2018) - Basden, A G; Brown, Anthony M; Chadwick, P M; Clark, P; Massey, R
Abstract: Astronomical adaptive optics (AO) systems are used to increase effective telescope resolution. However, they cannot be used to observe the whole sky since one or more natural guide stars of sufficient brightness must be found within the telescope field of view for the AO system to work. Even when laser guide stars are used, natural guide stars are still required to provide a constant position reference. Here, we introduce a technique to overcome this problem by using rotary unmanned aerial vehicles (UAVs) as a platform from which to produce artificial guide stars. We describe the concept that relies on the UAV being able to measure its precise relative position. We investigate the AO performance improvements that can be achieved, which in the cases presented here can improve the Strehl ratio by a factor of at least 2 for a 8 m class telescope. We also discuss improvements to this technique, which is relevant to both astronomical and solar AO systems.